PROGRAM EVALUATION OF THE FREE EDUCATION IN BALANGAN REGENCY - Akhriani . (LPPM Universitas Negeri Jakarta, 2017)
The research is aimed to investigate and analyze the contexts, input, process, and product of the free education program in the regency of Balangan. The research is an evaluative study by employing a CIPP model of program evaluation by Daniel L. Stufflebeam.The data of the study is collected from various sources which include the Education Department, headmasters, teachers, school committees, parents, students, and schooldocuments. The data is collected by utilizing observation, interview, questionnaire, and documentation.The results of the program evaluation show that: 1) the component of context which include the needs, goals, foundations, and program targets have met the evaluation criteria; 2) the component of input which consists of program plan, program structure, program management, and availability of the finance have met the evaluation criteria however the aspect of manpower particularly in the announcement of the finance that the schools have received, the use of the budget, and the announcement of free education through banners have not met the evaluation criteria; 3) the component of process have not met the evaluation criteria particularly the aspect of check clearing which include the indicator of accuracy of financial revenue to the school account, and the involvement of the school committees in designing the RAPS. On the aspect of budget use is the school’s announcement on the plan of financial use in the early of academic year. Meanwhile, on the aspect of budget responsibility is the school’s announcement on the use of the BOS/BOSDA in the school announcement boards. On the aspect of monitoring, the BOS/BOSDA management in the regency has analyzed the results of the monitoring whereas on the aspect of supervision the BOS/BOSDA management in the regency has carried out supervision to schools; and 4) the component of product involves the decrease of the numbers of the drop out children have met the evaluation criteria because the free education program has caused a significant effect on the decrease of the numbers of drop outs in the regency of Balangan